The Economics of Literature Study of Bidadari Bermata Bening Novel by Habiburrahman El Shirazy - Ahmad Bilal Almagribi; Imam Qalyubi (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2021)
This study aims to find the economic values contained in the novel Bidadari Bermata Bening by Habiburrahman El Shirazy. This research is a qualitative descriptive research that uses primary and secondary data sources. This study uses content analysis techniques by describing the contents of literary texts in novels and then relating them to economic theories. The results of the study found that there are many economic values contained in the novel Bidadari Bermata Bening, including: consumption, distribution, marketing, investment, production, and management. Consumption that occurs when the character buys tuna with a price difference that is not far from the market price. The distribution value is reflected in the giving of a certain amount of money for library books. Marketing is described when a merchant offers his product as an alternative to other products. Investments in novels are in the form of financing for children to study abroad. The production value is shown in figures who work in textile factories and in the operation of a service agency for the distribution of labor abroad. Management practices exist in collaboration between pesantren and local residents to provide lodging for student guardians.